The Relationship Between Colostrum Age and Lactation Period With Colostrum Production in Friesian Holstein (FH) Daily Cow at KPSP Setia Kawan, Pasuruan District - Sintang, Sekarwangi Nassida Kian; Surjowardojo, Puguh; Rifa'i, Rifa'i (Universitas Veteran Bangun Nusantara, 2023)
This research was conducted in the dairy farming in Dairy Cattle Cooperation Setia Kawan Wonosari Village, Tutur District, Pasuruan Regancy. The objective of this research was to analyze the correlation between colostrum age and lactation period with colostrum production on Friesian Holstein. The material used is 30 Friesian Holstein which are lactation, both the first lactation period to the third lactation period. The method used was the case study method and the data was collected data by direct observation of dairy cows. Data analyzed using regression analysis and correlation. The results show that the correlation between colostrum age and colostrum production has a regression the equation is Y = 9.8+0.75X, where r = 0.516 and R2 = 0.266 and the lactation period with colostrum production has a regression equation that is Y = 11.35+0.16X with r = 0.086 and R2 = 0.007. The average highest colostrum production in dairy cows was on the fourth day (12.61 ± 1.29 liters/head/day) and the highest colostrum production was in the third lactation (11.80 ± 1.68 liters/head/day). Based on these results it can be concluded that colostrum ages with colostrum production has a moderate positive correlation, while the lactation period with colostrum production has a very low positive correlation. Keywords : Lactation period, colostrum production, pregnant cow, friesian Holstein